In vitro Chemical and Fermentative Characteristics of Cynodon nlemfuensis Vanderyst and Guazuma ulmifolia Lam - Ley de Coss, Alejandro; Guerra Medina, Cándido Enrique; Martínez Córdova , Bérlan; Escobar España, Jos´´e Carlos; Morales Aguilar, Jonathan; Montañez-Valdez, Oziel Dante (Ecosistemas y Recursos Agropecuarios, 2025)
The objective consisted into the evaluation in vitro about the chemical and ferment characteristics mixing of the Estrella grass (Cynodon nlemfuensis; Cn) with an increase level of guacima (Guazuma ulmifolia; Gu). Four biodigester with a capacity fill of 2 000 mL individually, in which one, it was added 200 mL of mid cultive plus the treatments: T1: 20 g Cn (control); T2: 16 g Cn + 4.0 g Gu; T3: 12 g Cn+8 g Gu; T4: 8 g Cn + 12 g Gu. Treatments were inoculated with 20 mL of ruminal liquid, and they were kept during, 24, 48, 72 and 96 h in a temperature of 38 °C. The experiment design was a complement randomly measure with Tukey mean comparison test. In the results they were evaluated the productions of biogas, methane (CH4), volatile fatty acids (VFA), total bacterial concentrations (TBC) so the cellulolytic bacteria (CB), including the pH. The inclusion on guacima in the mixing allowed the reduction of fermentable cell walls, which result with less production of CH4. There were changes in the fermentation patrons of VFA, decreasing on the relation of acetate: propionate. The control treatment had the highest concentration of CB, without differences in the treatments based on the CBT. Although the pH which was up 6.0, it did not compromise the stability of the cultivation medias. The presence of guácima in the fermentations in vitro were contributed to mitigate the production of biogas and CH4, which get better the production of propionic acid.
Keywords: Biogas; fermentation; forage; livestock; tropic